Pengaruh Pemberian Suplemen Seng (Zn) dan Vitamin C Terhadap Kecepatan Penyembuhan Luka Pasca Bedah di Rumah Sakit Umum Daerah Kabupaten Sukoharjo - Rusjiyanto (Jurnal Kedokteran Indonesia, 2009)
Background: Patients admitted in hospital are generally distressed due to the infectious/inflammatory trauma. Similarly, the operative patients will encounter physiological stress due to hypermetabolism. In such condition, the need for nutrition will increase to accelerate the recovery process. This study aimed to examine if the Zn supplement administration alone or combination of Zn and Vitamin C affect the recovery rate of postoperative wound.Methods: This was a randomized controlled trial (RCT). A sample of 42 post-perative patients were assigned to 3 groups: one control group given placebo and 2 (two) treatment groups consisting of one groups given Zn supplement only and one given the combination of Zn + vitamin C. The assessment of wound recovery was done in 3 observations at day 3, 5, and 8 respectively. Anova and posthoc test were used to analyze the data.Results: Results showed no significant difference in mean value of post-operative wound recovery rate between observation I and II, but there was significant difference at observation III. At observation III, the posthoc test showed no significant difference between the supplement Zn group and the control group, but there was significant difference in wound recovery rate between Zn + vitamin C combination group and the control group (p= 0.040).Conclusion: Zn supplement alone administration does not affect the recovery rate of postoperative wound, but the combination of Zn and vitamin C supplement administration accelerates the postoperative wound recovery. Jurnal Kedokteran Indonesia: 1 (1): 64-75Keywords: Supplement, Zn, vitamin C, wound recovery